The Impact of Teacher’s Demo Lessons on Improving Teacher’s Performance and Lesson Effectiveness: an in-service training initiative introduced in a private American school in Al Ain - RAGAB, MOHAMED (2017)
The aim of this research is to study the impact of ‘teacher’s demo lesson program’ on improving pedagogy and lesson quality. The initiative is a part of the school in-service training programs for teachers’ professional development. Combining retooling, remodeling, and revitalizing approaches to teacher continuous professional development, adopting a more socio cultural view of teacher training programs, and using assumptions from various theories of adult learning, the current study presents a training initiative that involves teachers in both teaching and learning, and thus, helps them reconsider their classroom practices. The study took place in one of the private schools in Al Ain City in the Emirate of Abu Dhabi. The study sample included 139 middle school students and 8 middle school teachers. A mixed type approach was used for the data collection of the study. The results of the quantitative and qualitative research methods employed for the study suggest that the program has improved teachers’ overall performance and has a direct positive impact on lesson effectiveness. In spite of the high benefit of the initiative for teachers’ professional development, it cannot replace other in-service development programs that involve real classroom learning environment.